In vitro activity and in vivo efficacy of omadacycline against Plasmodium species - Michael S. Madejczyk; Susan E. Leed; Karl Kudyba; Alison Roth; Monica L. Martin; Patricia Lee; Diane Anastasiou; Jessica V. Pierce; Alisa W. Serio; Diana Caridha (Malaria Journal)
Abstract Background Doxycycline is currently the only tetracycline-class antibiotic recommended for malaria prophylaxis. Omadacycline, a semisynthetic aminomethylcycline approved for treatment of adults with community-acquired bacterial pneumonia and acute bacterial skin and skin structure infections, has a well-established safety profile. This study evaluated the in vitro activity of omadacycline against Plasmodium falciparum and Plasmodium cynomolgi and its in vivo efficacy against Plasmodium berghei in experimental malaria models to assess its potential as an antimalarial drug. Methods Fluorescence-based assays were used to assess the in vitro blood and liver stage activity of omadacycline and doxycycline against P. falciparum and P. cynomolgi laboratory clones. In vivo liver and early-stage blood stage efficacy were evaluated in a murine model of P. berghei infection, utilizing in vivo imaging of luciferase-expressing P. berghei (ANKA strain) sporozoites in female albino C57Bl/6 mice. Parasitaemia was monitored by flow cytometry for up to 30 days post-infection. Results Omadacycline demonstrated comparable in vitro activity to doxycycline against both drug-sensitive and drug-resistant P. falciparum clones, while doxycycline showed reduced activity against two drug-resistant clones. Notably, omadacycline exhibited superior anti-schizont activity in the P. cynomolgi liver stage assay. In the P. berghei murine model, omadacycline was efficacious in both liver and early blood stages compared to the untreated control group, and demonstrated improved survival compared to doxycycline. Conclusions Omadacycline demonstrated enhanced antimalarial efficacy over doxycycline in vitro in liver stage activity and in overcoming resistance in the blood stage, and in survival in an in vivo model of P. berghei infection. These findings support further investigation of omadacycline as a potential candidate for malaria prophylaxis and treatment.